Giving Up on Consciousness as the Ghost in the Machine - Halligan, Peter W.; Oakley, David A. (Frontiers in Psychology, 2021)
Consciousness as used here, refers to the private, subjective experience of being aware of our perceptions, thoughts, feelings, actions, memories (psychological contents) including the intimate experience of a unified self with the capacity to generate and control actions and psychological contents. This compelling, intuitive consciousness-centric account has, and continues to shape folk and scientific accounts of psychology and human behavior. Over the last 30 years, research from the cognitive neurosciences has challenged this intuitive social construct account when providing a neurocognitive architecture for a human psychology. Growing evidence suggests that the executive functions typically attributed to the experience of consciousness are carried out competently, backstage and outside subjective awareness by a myriad of fast, efficient non-conscious brain systems. While it remains unclear how and where the experience of consciousness is generated in the brain, we suggested that the traditional intuitive explanation that consciousness is causally efficacious is wrong-headed when providing a cognitive neuroscientific account of human psychology. Notwithstanding the compelling 1st-person experience (inside view) that convinces us that subjective awareness is the mental curator of our actions and thoughts, we argue that the best framework for building a scientific account is to be consistent with the biophysical causal dependency of prior neural processes. From a 3rd person perspective, (outside view), we propose that subjective awareness lacking causal influence, is (no more) than our experience of being aware, our awareness of our psychological content, knowing that we are aware, and the belief that that such experiences are evidence of an agentive capacity shared by others. While the human mind can be described as comprising both conscious and nonconscious aspects, both ultimately depend on neural process in the brain. In arguing for the counter-intuitive epiphenomenal perspective, we suggest that a scientific approach considers all mental aspects of mind including consciousness in terms of their underlying, preceding (causal) biological changes, in the realization that most brain processes are not accompanied by any discernible change in subjective awareness.